2017
DOI: 10.1002/jnm.2317
|View full text |Cite
|
Sign up to set email alerts
|

EMI effect simulation of braided cable network using a hybrid FDTD method

Abstract: This paper proposes a novel time domain numerical scheme based on a modified finite‐difference time‐domain (FDTD) method for electromagnetic interference (EMI) analysis of braided cable networks. In this method, a reasonable physical boundary condition is constructed by a transfer impedance model, while the spatial fields can be applied by way of adding incentive items into the transmission line equations. Besides, the full‐wave finite‐difference time‐domain(2, 4) method with thin wire model, transmission line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Modeling electromagnetic coupling effects is a crucial and challenging aspect of electromagnetic compatibility (EMC) analysis on complex electronic systems. 1 Extensive research and engineering experiments have demonstrated that electromagnetic interference (EMI) from wires would prevent sensitive sub-systems from expected action. [2][3][4][5][6][7][8] Generally, wire spacing is required to be provided to meet acceptable coupling.…”
Section: Introductionmentioning
confidence: 99%
“…Modeling electromagnetic coupling effects is a crucial and challenging aspect of electromagnetic compatibility (EMC) analysis on complex electronic systems. 1 Extensive research and engineering experiments have demonstrated that electromagnetic interference (EMI) from wires would prevent sensitive sub-systems from expected action. [2][3][4][5][6][7][8] Generally, wire spacing is required to be provided to meet acceptable coupling.…”
Section: Introductionmentioning
confidence: 99%